El entrenamiento en inteligencia emocional como base para disminuir los niveles de estrés laboral (2016)
This research aims to design an intervention proposal to lower levels of work stress based on training in Emotional Intelligence for administrative staff of the company Ikon Group SAS, located in the city of Medellin, recognizing the importance of Intelligence emotional and the great impact it has had in recent years. Similarly it considered work-related stress perceived as one of the great evils of the century in which we live. This study aims to relate the two concepts and examine the relationships you have at work, used a questionnaire to measure EI which measures the variables of self-awareness, managing emotions and motivation. After analyzing the data can be considered that the proposed objectives are achieved and it can be concluded that emotional intelligence has a positive regulatory effect against stress on staff. It is part of the report Psychosocial Risk made to employees of the company Ikon Group SAS in September 2015, which scored high levels of stress, therefore, the need for intervention is presented, which was oriented under five pillars of Emotional Intelligence Goleman proposed. (Goleman, 1998), addressed from two main areas: Personal skills such as self-awareness, self-regulation and self-motivation and a social skills are empathy and social skills, each pillar is made up of 25 competitions of which the proposed 13 competencies worked : emotional self-awareness, self-regulation, self-confidence, self-control, adaptability, achievement motivation, optimism, developing others, service orientation, communication, conflict management, leadership and ability team, which is to be achieved through different strategies the development of IE, such as coaching, conference, reflective workshops, meetings and conversations cycle.